IMPLEMENTASI ZAKAT PROFESI DI LINGKUNGAN KANTOR DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN SAMBAS PERSPEKTIF MASLAHAH MURSALAH - Wulan Sari, Bela; Asman; Miswinda (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Zakat is worship related to material possessions. These assets are usually in the form of money, commercial goods, livestock, crop products, and so on. Zakat is also a great potential that can be used as capital for state development as well as the predecessors of Islam. The benefit of paying zakat is to cleanse and purify the property they get so that they always get blessings. The formulation of the problem in this study is: how to Implement Professional Zakat at the Office of the Regional People's Representative Council of Sambas Regency and the Implementation of Professional Zakat at the Office of the Regional People's Representative Council of Sambas Regency Perspective of Maslahah Mursalah. This research uses descriptive qualitative research methods, and uses an empirical normative approach that examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) on a particular legal event that occurs in society. The result of this study is that the implementation of professional zakat in the Office of the Regional People's Representative Council of Sambas Regency has been carried out in accordance with the procedures for implementing professional zakat, and the point of view of the community about professional zakat is that the payment of professional zakat is very useful to help the community's economy and ease their living burden.